Proposing Publicity Leaving Church Apolitical Piety - Lasarus Umbu Labu Pinyawali; Purwo Santoso; Paulus Sugeng Widjaja (Asosiasi Ahli Filsafat Keilahian Indonesia, 2021)
This article seeks to release the Church from the false dichotomy of piety vs activeness in political issues, so that church members can optimally actualize piety and public responsibilities simultaneously. Apolitical piety has been running in GKS since its establishment on January 15, 1947, as the Dutch Reformed Church's evangelism legacy. Apolitical piety places the piety only as an individual's internal affair, not covering the public sphere. This discourse is a direct influence of Pietism, which began to develop in Europe in the 16th century. And Pietism itself was present as a response to Secularism, which originated in European society since the end Middle Ages. Like Pietism, Secularism also places the Church/religion and mystical aspects as personal human affairs because it doesn't want state life to be governed by or based on religion. But ideally, I view apolitical piety as the distorted discourse that should be abandoned and embrace new discourse: politics as an integral part of Church piety.